Faktor Penyebab dan Upaya Pengendalian Kebakaran Hutan di KPH Majalengka - Lailan Syaufina; Sofia Fitriana (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2021)
KPH Majalengka is one of the State-Owned Enterprises engaged in forest management business. KPH Majalengka also experienced disruptions arising from forest fires. BKPH Cibenda is an area with the highest fire incidence in KPH Majalengka with an area of 762.93 ha of the total area of forest fires covering 865.48 ha over the last five years (2013-2017). The purpose of this study was to analyze and describe the common cause of forest fires and control efforts in KPH Majalengka. The common cause of forest fires that often occur in BKPH Cibenda according to community perceptions are land clearing, burning deliberately, and grazing. Forms of forest fire prevention activities that have been conducted is socialization, training of forest fire control, warning signs, and firebreaks. Extinguishing activity that have been caried out by community is direct extinguishing and indirect outage, however the facilities of fire extinguishing do not fullfill the minimum aspect. Post-fire handling is often done by collecting damage and loss data, fire reporting, measurement of fire area and location sketching, analysis of damage level and writing event report in Letter A (LA). Keywords: BKPH Cibenda, forest fire, KPH Majalengka, land clearing, post fire